Rhamnolipid-enhanced Pseudomonas putida biofilm formation on hydrophilic surfaces with toluene as the bacterium's sole carbon source. (February 2018) - Katz, Haim; Farber, Ravit; Chaniel, Gilad; Ankar, Yaakov; Cohen, Haim; Cahan, Rivka
Abstract: The effect of surfactants on biofilm formation depends on the surfactant type, the bacterial strain and the carrier. In order to enhance the bioremediation process in the presence of a biosurfactant, it is crucial to choose the appropriate bacterial strain and carrier for biofilm formation. In the current research, a linear correlation was observed between toluene degradation by a planktonic Pseudomonas putida culture and increasing rhamnolipid concentrations. Biofilm viability on the hydrophilic surface after 24 h was 0.3 ± 0.007 (OD 540 nm), 1.4 fold higher than on the hydrophobic surface. The hydrophobicity of the bacterial cell wall for cultures that were grown on toluene in the presence and in the absence of rhamnolipid was determined by the contact angle of water measurement on the bacterial layer as well as by the bacterial adherence to a solution of hydrocarbon (BATH test). The results showed that the bacterial cell wall surface in the presence and absence of rhamnolipid is highly hydrophilic. The viability of the biofilm which was grown on hydrophilic surfaces: treated ELISA plate and coal bottom ash was 7-fold and 13-fold higher, respectively, when the cultures were grown on toluene in the presence of rhamnolipid as compared with its absence. In conclusion, the combination of hydrophilic surfaces, rhamnolipid and P. putida may serve as a good choice for enhancing the bioremediation process of toluene. Graphical abstract: Highlights: Rhamnolipid increased toluene degradation by planktonic P. putida culture. P. putida cell wall surface is highly hydrophilic in the presence and in the absence of rhamnolipid. In the presence of rhamnolipid, biofilm viability and biomass on hydrophilic plate were 7 and 2.7-fold higher, respectively. On the hydrophilic coal bottom ash there was 13-fold increase in the biofilm viability in the presence of rhamnolipid.